Field verification of low-level biochar applications as effective ameliorants to mitigate cadmium accumulation into Brassica campestris L from polluted soils - Zhang, Youchi; Liu, Shuang; Lin, Shanna; Reid, Brian J.; Coulon, Frederic; Cai, Chao (Frontiers in Environmental Science, 2023)
Introduction: Cadmium (Cd) has been recognized as a significant contributor to the pollution of farmland soils in China, and biochars have been reported to be effective in mitigating soil Cd pollution. However, most studies have been conducted in laboratory or greenhouse settings, not at a field scale, and the biochars used have been applied at unrealistically high amounts (>10 t/ha). Methods: In this research, three biochars: rice straw biochar (RSB), pig manure biochar (PMB) and rice husk biochar (RHB) were produced from readily available farm residues. Then the effects at low-level application (1.8 and 3.6 t/ha) on Cd were investigated in a field experiment cropped with rape (Brassica campestris L.). Results: Batch adsorption experiments indicated Cd adsorption capacity of three biochars followed the order of RSB (43.5 mg/g) > PMB (33.3 mg/g) > RHB (24.4 mg/g). Field experiment indicated biochar amendments could slightly change soil pH and cation exchange capacity (CEC); yet led to considerable and significant decreases in extractable Cd concentrations [reductions of: 43%–51% (PMB), 29%–35% (RSB) and 17%–19% (RHB)]. Reduced extractable Cd correlated with lower Cd concentrations in rape plants. PMB and RSB were more effective in decreasing Cd phytoaccumulation into edible parts of rape (>68% reduction) than RHB. Discussion: Low-level application of PMB or RSB could efficiently decrease the phytoaccumulation of Cd from soils into crops. These results demonstrate the reality of biochar-based remediation solutions to contribute to the mitigation of diffuse Cd contamination in farmland. The results also highlight the need to trail biochars in the presence of the soil to be targeted for remediation.